The role of meditation and mindfulness in the management of polycystic ovary syndrome: a scoping review - Rao, Vibhuti; Pena, Alexia; James, Annie; Phadke, Aashish; Grover, Jahnavi; Blendis, Ella; Choudhary, Nidhi; Kampegowda, Punith (Frontiers in Endocrinology, 2024)
Polycystic Ovary Syndrome (PCOS) presents multifaceted challenges affecting women's reproductive, metabolic, and psychological systems, consequently impacting their psychological and emotional well-being. The utilization of meditation and mindfulness interventions (MMIs) is found to be increasing for the management of PCOS. This scoping review systematically explored the current literature to identify the type and application of MMIs for PCOS management.A systematic search of literature was conducted using CINAHL, PsycINFO, Scopus, MEDLINE, and PubMed databases for identifying studies conducted on the usage of MMIs in women diagnosed with PCOS, irrespective of age. The comprehensive search identified 14 trials (comprising 17 citations) meeting inclusion criteria, involving 723 participants across various age groups. Among these, nine were randomized controlled trials (RCTs), while the remaining comprised non-RCTs. Several types of MMIs, including Rajayoga of Brahmakumaris, Yoga Nidra, OM cyclic meditation, unspecified forms of meditation, mindfulness-based stress reduction programs, mindful yoga, and mindfulness-based activities, were used. Outcomes were predominantly assessed in psychological domains (n=11), followed by anthropometric (n=9), quality of life (n=7), and metabolic metrics (n=7). The review findings suggest the integration of meditation with conventional treatment modalities. Preliminary data indicate that MMIs have the potential to improve psychosocial well-being and quality of life among PCOS-affected women. However, adequately powered studies with extended follow-up periods are required to investigate the mechanisms and therapeutic efficacy of MMIs, particularly concerning reproductive outcomes and weight management. Furthermore, diligent monitoring and reporting of adverse events and adherence are essential for a comprehensive understanding of MMI utilization in PCOS management.